Designing Curriculum of English Language Teaching for the Department of Sharia Tourism - Sungkawati Kardi Wahyuningsih (Asian Journal of Applied Education (AJAE), 2022)
This research and development aims to design an English language teaching curriculum in the Syari'ah Tourism study program at IAIN Takengon which includes the stages of situational analysis, function, purpose and usability, content, learning activities and assessment guidelines. The curriculum is designed based on situational analysis. This has a positive impact on the Gayo community. Competent team explaining this curriculum. facilities provided by the institution. Lessons are carried out by skilled and qualified teachers. The backgrounds, abilities, and enthusiasm of students are classified as similar. The device is adopted from Gayo's values ​​and beliefs. Student kits are designed to improve English language skills in promoting Sharia tourism in Gayo. The kit contains syllabus, materials, and assignment. Their learning activities are reading, writing, listening, and speaking. The experts validated the tools on the aspects of completeness of objectives, structure, content, skills, and methodology. The evaluation results state that the device is appropriate. The product can be used in other fields as English with special purposes assuming the convenience of situational analysis.